2017
DOI: 10.18632/oncotarget.17472
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA H19 induces hippocampal neuronal apoptosis via Wnt signaling in a streptozotocin-induced rat model of diabetes mellitus

Abstract: Defects in hippocampal synaptic plasticity and disorders of memory and learning are the central nervous system complications of diabetes mellitus (DM). Here, we used a streptozotocin-induced rat DM model to investigate the effects of long non-coding RNA H19 (lncRNA H19) on learning and memory and apoptosis of hippocampal neurons, and the involvement of the Wnt signaling. Our data demonstrate that lncRNA H19 is highly expressed in rats with DM. Over-expression of lncRNA H19 increased positioning navigation late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Along with the previously reported, NF-kappa B, IL-1b, and TNF-α ( Renard et al, 1997 ; Chandel et al, 2000 ). Meanwhile, the growing number of evidences have demonstrated the crucial role of lncRNAs in neurotransmission, memory structure, and synaptic plasticity in the brain ( Wang et al, 2018 ), such as the newly discovered lncRNA, MALAT1 ( Shang et al, 2018 ), NEAT1 ( Yan et al, 2018 ), and H19 ( Zhao et al, 2017 ). In a similar trend, lncRNAs may present biomarker for molecular diagnosis of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the previously reported, NF-kappa B, IL-1b, and TNF-α ( Renard et al, 1997 ; Chandel et al, 2000 ). Meanwhile, the growing number of evidences have demonstrated the crucial role of lncRNAs in neurotransmission, memory structure, and synaptic plasticity in the brain ( Wang et al, 2018 ), such as the newly discovered lncRNA, MALAT1 ( Shang et al, 2018 ), NEAT1 ( Yan et al, 2018 ), and H19 ( Zhao et al, 2017 ). In a similar trend, lncRNAs may present biomarker for molecular diagnosis of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we inferred that the levels of H19, miR-29b and FOXO4 might be correlated with the apoptosis of rat retinal Müller cells. To further investigate the mechanism of DR involving these genes, we concluded from recent reports that H19 plays important roles in the apoptosis of various cells, such as cardiomyocytes [33] , gastric cancer cells [34] , osteoblastic cell [35] , and hippocampal neuron of DM rat [17] . In our study, we also found that over-expression of H19 induced the apoptosis of rat retinal Müller cells and knockdown of H19 reversed HG stimulation on cell apoptosis and FOXO4 up-regulation, which means that HG stimulated the apoptosis of rat retinal Müller cells with H19 up-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, H19 serves as a carcinogenic gene in gastric cancer [14] , colorectal cancer [15] and glioma cells [16] . In addition, Zhao reported that H19 promotes the apoptosis of hippocampal neuron in streptozotocin-induced DM rat model via Wnt signaling [17] . However, the underlying mechanism of H19 involved in DR remains unclear.…”
mentioning
confidence: 99%
“…Studies have shown that more and more lncRNAs are abnormally expressed during the development and progression of diabetes and have the role of promoting or inhibiting the occurrence and development of diabetes and its complications . Therefore, studying lncRNA has decisive biological significance for understanding the occurrence and development of DCM and improving the ability to prevent and treat DCM.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“…60 Studies have shown that more and more lncRNAs are abnormally expressed during the development and progression of diabetes and have the role of promoting or inhibiting the occurrence and development of diabetes and its complications. [61][62][63][64][65][66] Therefore, studying lncRNA has decisive biological significance for understanding the occurrence and development of DCM and improving the ability to prevent and treat DCM. Through lncRNA expression profile analysis of C57BLKS/Jdb/db diabetic mouse model, Zhang et al found that there was a distinct lncRNA differential expression in diabetic mice, there were 354 significantly upregulated lncRNAs in the myocardium FIGURE 1 Long noncoding RNAs (lncRNAs) pertain to a heterologous class of transcripts and can be divided into diverse classes in the light of genomic location.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%